Decision Support System Fuzzy Analytic Hierarchy Process Method Studi Kasus Pemilihan Vendor Kemasan Terbaik - Najmuddin Najmuddin; Arief Herdiansah (Jurnal Informatika, 2021)
Packaging is a component that must be considered because it can affect (visually) the customer in determining the decision to buy the product being offered. The quality of the raw materials used, the shape and aesthetics of the packaging must be in accordance with the wishes of customers who want the safety and beauty of product packaging without affecting the quality of the food stored in it. To be able to help companies have quality packaging, a decision support system (SPK) is needed that can quickly and precisely choose the best packaging vendor. The results of this study have proven that the Fuzzy Analytic Hierarchy Process Method has been able to assist users in the process of selecting the best packaging vendor